1995
DOI: 10.1139/o95-124
|View full text |Cite
|
Sign up to set email alerts
|

Fungal ribotoxins: a family of naturally engineered targeted toxins?

Abstract: alpha-Sarcin, mitogillin, and restrictocin are small (approximately 17 kDa) basic robosome-inactivating proteins (RIPs) produced by the Aspergilli that catalytically inactivate the large ribosomal subunits of all organisms tested to date. These three fungal ribotoxins act as specific ribonucleases by hydrolyzing one single phosphodiester bond in the universally conserved alpha-sarcin domain of 23-28S rRNAs and are among the most potent inhibitors of protein synthesis known. Previous molecular studies of riboto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 65 publications
2
61
0
1
Order By: Relevance
“…Mitogillin is a small basic protein of approximately 18 kDa with cytotoxic activity released by A. fumigatus (16,17,31). Together with the related toxins A. fumigatus allergen I (AspfI), restrictocin from Aspergillus restrictus (20), and ␣-sarcin from Aspergillus giganteus (26), mitogillin is a member of a family of conserved RNases that cleave a single phosphodiester bond of the 29S rRNA of eukaryotic ribosomes (11,16,17).…”
mentioning
confidence: 99%
“…Mitogillin is a small basic protein of approximately 18 kDa with cytotoxic activity released by A. fumigatus (16,17,31). Together with the related toxins A. fumigatus allergen I (AspfI), restrictocin from Aspergillus restrictus (20), and ␣-sarcin from Aspergillus giganteus (26), mitogillin is a member of a family of conserved RNases that cleave a single phosphodiester bond of the 29S rRNA of eukaryotic ribosomes (11,16,17).…”
mentioning
confidence: 99%
“…These mutational studies have revealed the involvement of several residues, which are conserved among the different microbial extracellular RNases, in catalysis. Thus, it is well known that His137 and Glu96 are the only residues that are essential for the cleavage reaction performed by α-sarcin [35,45,[70][71][72][73][74][75], whereas His-50, Tyr-48, Arg-121, and Leu-145 mostly contribute to the stabilization of the transition state [45][46][47][48], as stated above. Most of these residues are located in the central β-sheet and their side-chains point towards the concave face of the protein structure where the substrate is supposed to dock [29].…”
Section: Structural Featuresmentioning
confidence: 85%
“…α-Sarcin is able to inactivate the ribosomes of a great variety of organisms in cell-free systems [4,35], but it displays marked selectivity when intact cells are used as targets. This specificity seems to be determined by its ability to penetrate cells, as explained above.…”
Section: Cytoxicity Against Intact Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these are two proteins that have been used in this study: the 18-kDa immunoglobulin E (IgE)-binding protein Aspf1 and the glycosylphosphatidylinositol-anchored extracellular cell wall glucanase Crf1 (2). Aspf1 is a member of a family of conserved RNases that cleave defined phosphodiester bonds of the 28S rRNA of eukaryotic ribosomes (3,16). In this study, we analyzed different aspects of the response of human monocyte-derived DCs to Crf1 and, especially, Aspf1.…”
mentioning
confidence: 99%